Message received: Asian Americans' racial, ethnic, and national identity centrality before and after the 2016 election. Issue 2 (4th March 2022) - Farrell, Allan; Casarez, Raul S.; Zhang, Xiaorui; Mehta, Sharan Kaur
Abstract: Many different external factors shape Asian American identity. However, the effect of political elections on racial, ethnic, and national identities has been understudied. This research explores whether political elections represent moments of exogenous shock that can shape the importance of three different dimensions of identities for Asian Americans. This study uses data from the 2016 National Asian American Survey ( n = 3, 643) to test for a relationship between the racialized rhetoric surrounding the 2016 U.S. presidential election and the aforementioned aspects of Asian American identity. Regression analyses suggest that the election shaped patterns of centrality of racial, national and ethnic identity among Asian Americans, albeit differently across ethnic groups. Specifically, American identity centrality increased for Chinese respondents post-election relative to pre-election, but did not shift significantly for any other group. On the other hand, racial identity centrality significantly decreased for Filipino and Vietnamese respondents post-election, while other groups did not experience a significant change in their racial identity centrality. Finally, ethnic identity centrality only decreased significantly among Korean respondents post-election. This research suggests that these identities among Asian Americans are sensitive to external events, such as political elections, and that the effects of racialized political rhetoric vary across ethnicity.